Contextual factors associated with neonatal pain responses: clinical observational study - Zhan, Xinling; Zhu, Nanxi; Long, Bingjie; Wang, Zechuan; Miao, Rui; Wang, Gang; Chen, Juan; Huang, Chi; Xiong, Lu; Huang, Yi; Lam, Simon Ching; Wang, Lianhong; et al. (Frontiers in Pediatrics, 2025)
ObjectivesThis study aimed to identify the contextual factors of neonatal pain responses and provide clinical medical staff with evidence regarding effective means of evaluating neonatal pain and strengthen clinical pain management.MethodsTwo trained nurses independently used the Neonatal Infant Pain Scale (NIPS) to assess the pain scores of 198 neonates after they underwent painful medical procedures. Univariate linear regression analysis was performed to analyze the correlation between contextual factors and NIPS scores. Variables with statistically significant differences (p < 0.2) after univariate linear regression analysis were selected as independent variables, and the NIPS score was used as the dependent variable. Multiple linear regression was used to determine the salient factors associated with neonatal pain responses. This study was registered at the Chinese Clinical Trial Registry (ChiCTR2300074086).ResultsUnivariate linear regression analysis showed that the NIPS scores were associated with days after birth, types of painful procedures, Apgar scores at 1 min after birth, and gestational age (GA) (p < 0.2). Multiple regression analysis showed that Apgar score at 1 min after birth (β = 0.272, p < 0.001) and GA (β = 0.503, p < 0.001) were independent associated factors of neonatal pain responses. Neonates with low Apgar scores at 1 min after birth and younger GA had less pronounced pain responses.ConclusionsThe Apgar score at 1 min after birth and GA affected the neonatal pain responses. In this regard, the current clinical method of pain assessment solely through observation of neonatal pain responses is occasionally inaccurate. The Apgar score at 1 min after birth and GA should be considered in determining the neonatal pain status and hence enhance the quality of neonatal pain management.